Tradisi Tea Pai dengan Penyajian Green With Cinnamon Tea (Grecin Tea) Sebagai Minuman Tradisional Upacara Pengantin Tionghoa. - Ermadi, Tifani; Sri Dwiyanti; Mutimmatul Faidah; Dindy Sinta Megasari (Jurnal Tata Rias, 2026)
Indonesia's rich ethnic and cultural diversity has given rise to a variety of traditional wedding ceremonies, each steeped in unique symbolic meanings and reflecting distinct cultural identities. Among these traditions, Tea Pai, the tea-serving ritual in Chinese wedding customs, holds profound philosophical and spiritual significance. However, the challenges of modernization demand innovations that preserve the essence of this tradition while considering health aspects and increasing the practicality of serving. This study aims to introduce an innovative beverage formulation, Grecin Tea (Green With Cinnamon Tea), specifically designed for integration into the Tea Pai ceremony. This study used a qualitative approach with data collection techniques through product evaluation, which included panelist assessments of taste, aroma, and color, as well as microbiological safety testing. The results showed that Grecin Tea received a "like" rating from the majority of respondents and a "very like" rating from several panelists. Laboratory tests showed that the product was free from pathogenic microbes and suitable for consumption. Independent validators assessed the composition of taste, aroma, and color indicators as good. Visitors to the Grecin Tea booth at the 2021 RUPASAMPURNA Cipta Karya event also received positive feedback, providing "good" testimonials and affirming the product's safety. Overall, Grecin Tea successfully blends traditional values with modern demands, presenting a beverage that is not only symbolic and healthy, but also practical to prepare.